(untitled) (Scientific journal of the Fergana State University, 2024)
This article evaluates information security risk management processes, emphasizing the critical role of risk assessment in safeguarding organizational assets. It details the stages of risk assessment–identification, analysis, evaluation, and treatment–and scrutinizes tools such as CRAMM, FRAP, RiskWatch, MSAT, and CORAS for their effectiveness across various organizational settings. A comparative analysis assesses each toolʼs strengths and limitations, providing guidance for organizations to select appropriate methodologies that align with ISO 31000 standards. This study aims to help organizations adapt to evolving threats and maintain compliance by enhancing their security frameworks through suitable risk assessment practices. The insights offered serve as a strategic resource for continuous improvement in information security management.